Conceptualization of Short Supply Chains: Contributions from the Southeast of the Province of Buenos Aires, Argentina - Cendón, Maria Laura (2023)
The COVID-19 pandemic strengthened the discussion around the hegemonic global food model. At the same time, it gave rise to the proliferation of innovative rural-periurban-urban interactions in the supply of cities, which have accounted for changes in the social relations of production, circulation, and consumption of food. There are different approaches that refer to these processes, and introduce concepts such as short supply chains and alternative food networks. However, there are no definitions accepted universally by the scientific community. Similarly, there is no conceptualization at the local level that would enable a systematization of experiences. In the light of this, an opportunity to reflect critically and propose a contextualized conceptualization has been opened up. The aim of this article is to conceptualize the term short food supply chain and the construction of a typology for the southeast of the province of Buenos Aires, Argentina. This work was based on a bibliographic review and the identification of different dimensions to formulate a definition that allows the systematization of experiences, their characterization, quantification, and consequent visibility. This way, material will be generated for the development of public policies aiming at strengthening the sector.